Evaluations of Auto-Focusing Methods under a Microscopic Imaging Modality for Metaphase Chromosome Image Analysis - Yuchen Qiu; Xiaodong Chen; Yuhua Li; Wei R. Chen; Bin Zheng; Shibo Li; Hong Liu (Analytical Cellular Pathology)
Background: Auto-focusing is an important operation in high throughput imaging scanning. Although many auto-focusing methods have been developed and tested for a variety of imaging modalities, few investigations have been performed on the selection of an optimal auto-focusing method that is suitable for the pathological metaphase chromosome analysis under a high resolution scanning microscopic system.